Effects of PEGylation on capture of dextran-coated magnetic nanoparticles in microcirculation - Chiu, Chien-Yu; Chung, Tze-Wen; Chen, Si-Yi; Ma, Yunn-Hwa (International journal of nanomedicine, 2019)
Magnetic nanoparticles (MNPs) can be localized against hemodynamic forces in blood vessels with the application of an external magnetic field. In addition, PEGylation of nanoparticles may increase the half-life of nanocomposites in circulation. In this work, we examined the effect of PEGylation on the magnetic capture of MNPs in vivo. Laser speckle contrast imaging and capillaroscopy were used to assess the magnetic capture of dextran-coated MNPs and red blood cell (RBC) flow in cremaster microvessels of anesthetized rats. Magnetic capture of MNPs in serum flow was visualized with an in vitro circulating system. The effect of PEGylation on MNP-endothelial cell interaction was studied in cultured cells using an iron assay. In microcirculation through cremaster muscle, magnet-induced retention of 250 nm MNPs was associated with a variable reduction in RBC flow, suggesting a dynamic coupling of hemodynamic and magnetic forces. After magnet removal, faster restoration of flow was observed in PEG(+) than PEG(-) group, which may be attributed to a reduced interaction with vascular endothelium. However, PEGylation appears to be required for magnetic capture of 50 nm MNPs in microvessels, which was associated with increased hydrodynamic diameter to 130±6 nm in serum, but independent of the ς-potential. These results suggest that PEGylation may enhance magnetic capture of smaller MNPs and dispersion of larger MNPs after magnet removal, which may potentially affect the targeting, pharmacokinetics and therapeutic efficacy.